Striatal function scrutinized through the PAN-TAN-FSI triumvirate - Apicella, Paul; Martel, Anne-Caroline; Marche, Kevin (Frontiers in Cellular Neuroscience, 2025)
Understanding the information encoded by distinct components of the neuronal circuitry in the striatum represents an avenue for elucidating the role of this subcortical region in adaptive behavior and its dysfunction in pathological conditions. In behaving animals, conventional single neuron recordings generally differentiated between three main electrophysiologically identified neuron subtypes in the striatum, referred to as phasically active neurons (PANs), tonically active neurons (TANs), and fast-spiking interneurons (FSIs), assumed to correspond to GABAergic spiny projection neurons, cholinergic interneurons, and parvalbumin-containing GABAergic interneurons, respectively. Considerable research has been devoted to exploring the behavior-related activities of neurons classified electrophysiologically into PANs, TANs, and FSIs in animals engaged in task performance, mostly monkeys. Although precise neuron identification remains a major challenge, such electrophysiological studies have provided insights into the functional properties of presumed distinct striatal neuronal populations. In this review, we will focus on current ideas about the functions subserved by these neuron subtypes, emphasizing their link to specific aspects of behaviors. We will also underline the issues that are yet to be resolved regarding the classification of striatal neurons into distinct subgroups which emphasize the importance of considering the potential overlap among electrophysiological characteristics and the molecular diversity of neuron types in the striatum.